Hasil Analisis Kebutuhan Bahan Ajar Pada Mapel IPA Kelas IV SDN Badal Pandean - Zunaidah, Farida Nurlaila; Margareta, Intan Viona; Sulistyowati, Tutut Indah (PTK: Jurnal Tindakan Kelas, 2024)
This research was conducted to evaluate the need for teaching materials in science learning for fourth-grade students at SDN Badal Pandean, specifically on the topic of Changes in the State of Matter. The urgency of this research lies in the pressing need to provide more effective teaching materials to support student learning. The objective of this study is to identify the challenges faced by students in mastering the subject matter, evaluate the effectiveness of the teaching materials currently in use, and determine the need for developing process-skills-based teaching materials. This study employed a descriptive qualitative method, involving data collection through interviews, observations, questionnaires, and pre-tests. The findings revealed that 62.5% of students failed to meet the Minimum Mastery Criteria (MMC) in the pre-test and faced difficulties in understanding the material. Moreover, the student worksheets (LKPD) used in the learning process were found to be inadequate as they lacked essential components to support effective learning. The development of teaching materials that are better tailored to students' characteristics and enriched with practical activities is highly necessary to enhance students' understanding of science concepts. These findings are expected to serve as a guide for teachers in designing effective and relevant teaching materials to meet students' needs.